Leveraging cryoablation and checkpoint inhibitors for high-risk triple negative breast cancer - Sardela de Miranda, Flávia; Castro, Maribel; Remmert, Nicole; Singh, Sharda P.; Layeequr Rahman, Rakhshanda; Melkus, Michael W. (Frontiers in Immunology, 2023)
Breast cancer is the second most common cancer among women in the United States in which the standard of care treatment is surgery with adjunctive therapy. Cryoablation, which destroys the tumor using extremely cold temperatures while preserving the potential tumor antigens, is a promising alternative to surgical resection. It is less invasive, cosmetically appeasing, cost-effective, and capable of contributing to the abscopal effect -the immune response targeting potential distant metastasis. However, to maximize the immunologic benefit of cryoablation in biologically high-risk breast cancers, combination with therapies that enhance immune activation, such as immune checkpoint inhibitors (ICIs) may be necessary. This mini review describes the fundamentals of cryoablation and treatment with ICIs, as well as discuss the caveats in both strategies and current clinical trials aimed to improve this approach to benefit patients.